Capitalising on Spatiality in European Transport Corridors. (2nd August 2013) - Witte, Patrick; Van Oort, Frank; Wiegmans, Bart; Spit, Tejo
Abstract: After half a century of corridor development in Europe, the corridor concept is well‐established in the academic discourse on transportation. Transport corridors have also been common practice in European transport policy since the creation of a borderless Europe in the 1990s. What is largely lacking in present‐day research on European transport corridors is a consideration of a sector‐transcendent and comprehensive spatial approach. We argue that adopting such an approach is beneficial to a valued analysis of European transport corridors, especially in the light of EU cohesion policy, agglomeration effects and place‐based development. Also, negative external effects of persisting bottlenecks on welfare and quality of life in transport corridors should be better assessed and contextualised. This paper therefore suggests that policy can and should capitalise more on spatiality in corridors.